Comprehensive comparison between 222 CTLA-4 haploinsufficiency and 212 LRBA deficiency patients: a systematic review. (3rd May 2021) - Jamee, M; Hosseinzadeh, S; Sharifinejad, N; Zaki-Dizaji, M; Matloubi, M; Hasani, M; Baris, S; Alsabbagh, M; Lo, B; Azizi, G
Summary: Cytotoxic T lymphocyte antigen 4 (CTLA-4) haploinsufficiency (CHAI) and lipopolysaccharide-responsive beige-like anchor (LRBA) deficiency (LATAIE) are newly identified inborn errors of immunity with shared molecular pathomechanisms and clinical manifestations. In this review, we aimed to provide differential comparisons regarding demographic, clinical, immunological and molecular characteristics between these two similar conditions. A literature search was conducted in PubMed, Web of Science and Scopus databases and included studies were systematically evaluated. Overall, 434 (222 CHAI and 212 LATAIE) patients were found in 101 eligible studies. The CHAI patients were mainly reported from North America and western Europe, while LATAIE patients were predominantly from Asian countries. In CHAI, positive familial history ( P  < 0·001) and in LATAIE, consanguineous parents ( P  < 0·001) were more common. In CHAI patients the rates of granulomas ( P  < 0·001), malignancies ( P = 0·001), atopy ( P = 0·001), cutaneous disorders ( P  < 0·001) and neurological ( P = 0·002) disorders were higher, while LATAIE patients were more commonly complicated with life-threatening infections ( P = 0·002), pneumonia ( P = 0·006), ear, nose and throat disorders ( P  < 0·001), organomegaly ( P = 0·023), autoimmune enteropathy ( P = 0·038) and growth failure ( P  < 0·001). Normal lymphocyte subsets and immunoglobulins except low serum levels of CD9 + B cells (14·0 versus 38·4%, P <  0·001), natural killer (NK) cells (21 versus 41·1%, P <  0·001), immunoglobulin (Ig)G (46·9 versus 41·1%, P =  0·291) and IgA (54·5 versus 44·7%, P =  0·076) were found in the majority of CHAI and LATAIE patients, respectively. The most frequent biological immunosuppressive agents prescribed for CHAI and LATAIE patients were rituximab and abatacept, respectively. Further investigations into the best conditioning and treatment regimens pre- and post-transplantation are required to improve the survival rate of transplanted CHAI and LATAIE patients. Graphical Abstract: